The balance of power between food manufacturers and retailers - Jacqueline L. Spence; A. W.F. Fourie (South African Journal of Business Management, 1995)
There is an ongoing debate as to who in the South African food sector holds the most power - the manufacturer or the retailer. This debate becomes particularly heated at times when the price of food is seen to be rising disproportionately to the overall inflation rate, as evidenced in 1991. This research contributes to the debate surrounding the balance of power. The overall balance of power is seen to be made up of three components: power - the ability of member A to alter the decisions of member B; non-coercive sources of power - the ability to give assistances/rewards; and coercive sources of power - the ability to apply punishments. It was found that manufacturers are strongest on the power dimension, retailers have the greatest strength in the coercive sources of power dimension, and neither retailers nor manufacturers have the upper hand in respect of non-coercive sources of power. The overall balance of power is, however, perceived to be dynamic in nature and likely to change in future due to Issues such as changing consumer profiles and the installation and commissioning of sophisticated information systems by retailers.
Keywords: 650